Judicial Immunity of diplomatic missions - Alamoudi, Abrar Jamal (Journal of Economic, Administrative and Legal Sciences, 2024)
The study addresses Judicial immunity of diplomatic missions. The subject matter of the study is focused on the need to identify the immunities to each of the diplomatic mission and the diplomatic envoy in order to provide the necessary protection for the members of the diplomatic mission when they carry out their job duties. The study is divided into three chapters. The introductory chapter handles the concept of diplomatic immunity and the legal basis for granting it. In the second chapter we can learn about judicial immunities of a diplomatic envoy. Finally, the third chapter indicates provisions and applications of criminal judicial immunity. The study aims mainly to clarify the aspects of the judicial immunity of the diplomatic mission. We can see that the study depended on descriptive and analytical method. It concluded multiple results; the most important of them is that the stability of international custom since ancient times to grant diplomatic envoys a set of immunities and diplomatic privileges as a protection for them from any pressure or harm that prevents them from carrying out their job duties. The diplomatic judicial immunities enjoyed by the diplomatic envoys vary between criminal judicial immunity, civil judicial immunity, and administrative judicial immunity. The restrictions and exceptions to the immunities and privileges enjoyed by the headquarters of the diplomatic mission and its appurtenances are based on the concept of national security and national sovereignty. The study recommended establishing a diplomatic criminal court to look into crimes committed by diplomats especially serious crimes that may threaten the national security of states. Moreover, the need to amend some provisions of the Vienna Convention on Diplomatic Relations, especially those related to judicial immunity to keep pace with developments in our current era. Also establishing an international agreements aimed at achieving a balance between the immunities and privileges granted to diplomatic envoys and ensuring that those concerned obtain their rights.